MENGUNGKAP JEJAK HIJAU BUMN INFRASTRUKTUR: SEJAUH MANA KOMITMEN LINGKUNGAN TERCERMIN DALAM LAPORAN KEBERLANJUTAN? - Salsabila, Dwi; Bandiyono, Agus (Indonesian Accounting Research Journal, 2024)
Sustainability reports have become an essential means for organization to disclose the environmental impact of their activities. This study aims to analyze the extent to which State-Owned Enterprises (SOEs) in the infrastructure services sector have reported their Environment, Social, and Governance (ESG) activities in accordance with the Global Reporting Initiative (GRI) 300 standard. This research uses qualitative content analysis of the 2023 sustainability reports of three SOEs in the infrastructure services sector. The results of the analysis show that the level of disclosure related to the environment (GRI 300) is still not optimal, especially in the aspects of biodiversity and supplier environmental assessment. PT Adhi Karya showed the best performance in GRI 300 disclosure, followed by PT Hutama Karya and PT Waskita Karya. This research contributes to SOEs in improving the quality of their sustainability reports in accordance with GRI standards, as well as for policymakers in formulating more effective sustainability reporting policies in Indonesia.